Longitudinal characterization of the tumoral microbiome during radiotherapy in HPV-associated oropharynx cancer. (January 2021) - Bahig, Houda; Fuller, Clifton D.; Mitra, Aparna; Yoshida-Court, Kyoko; Solley, Travis; Ping Ng, Sweet; Abu-Gheida, Ibrahim; Elgohari, Baher; Delgado, Andrea; Rosenthal, David I.; Garden, Adam S.; Frank, Steven J.; et al.
Highlights: The microbiome of HPV+ oropharynx cancer exhibits reduced alpha diversity during radiotherapy. The baseline tumor bacterial profiles of smokers vs. non-smokers are inherently different. Eark High baseline alpha diversity may predict early response to radiation and should be investigated. Alteration of the tumor microbiome composition occurs as early as in the first week of radiotherapy. Abstract: Purpose: To describe the baseline and serial tumor microbiome in HPV-associated oropharynx cancer (OPC) over the course of radiotherapy (RT). Methods: Patients with newly diagnosed HPV-associated OPC treated with definitive radiotherapy +/− concurrent chemotherapy were enrolled in this prospective study. Using 16S rRNA gene sequencing, dynamic changes in the tumor site microbiome during RT were investigated. Surface tumor samples were obtained before RT and at week 1, 3 and 5 of RT. Radiological primary tumor response at mid-treatment was categorized as complete (CR) or partial (PR). Results: Ten patients were enrolled, but 9 patients were included in the final analysis. Mean age was 62 years (range: 51–71). As per AJCC 8th Ed, 56%, 22% and 22% of patients had stage I, II and III, respectively. At 4-weeks, 6 patients had CR and 3 patients had PR; at follow-up imaging post treatment, all patients had CR. The baseline diversity of the tumoral versus buccal microbiome was not statistically different. For the entire cohort, alpha diversity was significantly decreased over the course of treatment (p = 0.04). There was a significant alteration in the bacterial community within the first week of radiation. Baseline tumor alpha diversity of patients with CR was significantly higher than those with PR (p = 0.03). While patients with CR had significant reduction in diversity over the course of radiation (p = 0.01), the diversity remained unchanged in patients with PR. Patients with history of smoking had significantly increased abundance of   Kingella  (0.05) and lower abundance of  Stomatobaculum  (p = 0.03) compared to never smokers. Conclusions: The tumor microbiome of HPV-associated OPC exhibits reduced alpha diversity and altered taxa abundance over the course of radiotherapy. The baseline bacterial profiles of smokers vs. non-smokers were inherently different. Baseline tumor alpha diversity of patients with CR was higher than patients with PR, suggesting that the microbiome deserves further investigation as a biomarker of radiation response.